2022
DOI: 10.1007/s42979-022-01150-9
|View full text |Cite
|
Sign up to set email alerts
|

Ten GIS-Based Solutions for Managing and Controlling COVID-19 Pandemic Outbreak

Abstract: The coronavirus (COVID-19) pandemic has caused disastrous results in most countries of the world. It has rapidly spread across the globe with over 156 million cumulative confirmed cases and 3.264 million deaths to date, according to World Health Organization (WHO) Coronavirus Disease (COVID-19) Dashboard. With these huge amounts of causalities in the world, Geographic Information Systems (GIS) as a computer-based analyzer could help governments, experts, medical staff, and citizens to prevent and respond to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 117 publications
0
4
0
1
Order By: Relevance
“…The results revealed that these applications could be used for health service monitoring and allocation, e.g., the number of hospital and the number of available beds, which facilitated efficient management. However, this research did not support assistance for people in each area in terms of items, food, and herbs [34].…”
Section: Applying Gis To Covid-19mentioning
confidence: 59%
“…The results revealed that these applications could be used for health service monitoring and allocation, e.g., the number of hospital and the number of available beds, which facilitated efficient management. However, this research did not support assistance for people in each area in terms of items, food, and herbs [34].…”
Section: Applying Gis To Covid-19mentioning
confidence: 59%
“…The coronavirus disease 2019, which is also widely known as COVID-19, remains a Public Health Emergency of International Concern (PHEIC) [ 1 ]. To date, as of 31st December 2022, there are a total of 730 763 167 cases and 6 697 328 deaths globally [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…Their study evaluated the most suitable techniques of statistical methods, predictive models, geographical information system (GIS)-based solutions and emerging technologies applicable to decision-making tools. 19 Lei et al (2019) researched the dynamic trend of risk transmission within the transnational supply chain to prevent the spread of risks. They proposed an improved susceptible-infectious-susceptible (SIS) model combined with a complex network model and an optimised approach to the selection of risk control strategies.…”
Section: Introductionmentioning
confidence: 99%